1984
DOI: 10.1007/bf00553165
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the selective benzodiazepine antagonist Ro 15-1788 in man

Abstract: The pharmacokinetics of the selective benzodiazepine antagonist Ro 15-1788 has been studied in 6 healthy male volunteers following a single intravenous dose of 2.5 mg. The drug was only slightly bound to plasma proteins (40 +/- 8%, mean +/- SD). A negligible amount (less than 0.2% of the dose) of unchanged drug was recovered in urine. Hepatic elimination was rapid, as shown by a short t1/2 of 0.9 +/- 0.2 h, and high total plasma and blood clearances of 691 +/- 216 ml/min and 716 +/- 199 ml/min, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
1

Year Published

1986
1986
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
4
21
1
Order By: Relevance
“…Flumazenil is extensively metabolized in the liver (18,19). The proposed metabolic pathways of flumazenil lead to formation of a free acid (Ro 15-3890), alcohol (Ro 15-4965) and desmethyl (Ro 15-5528) compounds after hydrolysis and oxidation respectively (20).…”
Section: Methodsmentioning
confidence: 99%
“…Flumazenil is extensively metabolized in the liver (18,19). The proposed metabolic pathways of flumazenil lead to formation of a free acid (Ro 15-3890), alcohol (Ro 15-4965) and desmethyl (Ro 15-5528) compounds after hydrolysis and oxidation respectively (20).…”
Section: Methodsmentioning
confidence: 99%
“…This effect was only visible by regarding the time period of 60 min after injection, when Ro 15-1788 is detectable in plasma, as can be derived from our kinetic data (Klotz et al, 1984), or over shorter periods (30 min).…”
Section: Discussionmentioning
confidence: 87%
“…In the first clinical trials it was found that this drug could reverse the sedative-hypnotic effects of clonazepam, diazepam, flunitrazepam, midazolam, and other benzodiazepines rapidly ( see Hunkeler et al, 1981;Bonetti et al, 1982;Klotz et al, 1985). The very short duration of action corresponds weil to the elimination half-life time of about 0.97 ± 0.2 hours (Klotz et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations